1991
DOI: 10.1111/j.1476-5381.1991.tb09840.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological modulation of endothelin‐induced contraction of guinea‐pig isolated airways and thromboxane release

Abstract: 1The aim of the present experiments was to study the possible involvement of known bronchoconstrictor substances in mediating the myotropic action of endothelin-l (ET-1, human-porcine endothelin) in guinea-pig isolated airways. 2 ET-1 (1-100nm) caused a dose-dependent contraction of guinea-pig trachea, upper bronchus and parenchyma. The contractions developed slowly, reaching maximal values 4-6 min after addition of the peptide. 3 The contractile action of ET-1 was significantly attenuated by indomethacin (10u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
9

Year Published

1991
1991
1999
1999

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 48 publications
(66 reference statements)
1
20
0
9
Order By: Relevance
“…Recent evidence suggests that PAF may be one of these mediators. Indeed, certain effects of endothelin-1 can be attenuated by PAF receptor antagonists (Lagente et al, 1989;Takayashu et al, 1989;Terashita et al, 1989;Battistini et al, 1990;Filep et al, 1991), and endothelin-1-induced PAF synthesis has also been reported (Lopez-Farre et al, 1990 (Voelkel et al, 1986). It is also possible that the bioavailability of these antagonists is different (Kubes et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests that PAF may be one of these mediators. Indeed, certain effects of endothelin-1 can be attenuated by PAF receptor antagonists (Lagente et al, 1989;Takayashu et al, 1989;Terashita et al, 1989;Battistini et al, 1990;Filep et al, 1991), and endothelin-1-induced PAF synthesis has also been reported (Lopez-Farre et al, 1990 (Voelkel et al, 1986). It is also possible that the bioavailability of these antagonists is different (Kubes et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, PAF receptor antagonists have been reported to attenuate the bronchoconstrictor action of endothelin-1 in the guinea-pig both in vivo (Lagente et al, 1989) and in vitro (Battistini et al, 1990;Filep et al, 1991), to inhibit endothelin-1-induced increase in intracellular free calcium levels in cultured smooth muscle cells (Takayashu et al, 1989) and to protect against endothelin-1-induced sudden death in mice and rats (Terashita et al, 1989). Furthermore, endothelin-1 has recently been shown to stimulate PAF synthesis in glomerular mesangial cells (Lopez-Farre et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…A tone-dependent change in sensitivity of the trachea to NO cannot be ruled out at present. The possibility that epithelium removal led to decreased formation of bronchorelaxant prostanoids seems unlikely as under the same experimental conditions, indomethacin significantly attenuated the contractile action of ET-1 (Filep et al, 1991). Another explanation might be that under resting conditions the epithelium may function primarily as a protective (diffusion and/or metabolic) barrier, reducing the contact between agonists and airway smooth muscle.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, the relaxation experiments were performed either in the absence or in the presence of BM 13505 (5 tLM), a specific thromboxane A2/prostaglandin H2 receptor antagonist (Patscheke et al, 1987). At the concentration employed, BM 13505 neither affects prostanoid formation (Patscheke et al, 1987;Filep et al, 1991) nor interferes with the biological responses to other bronchoactive agents, including platelet-activating factor, 5-hydroxytryptamine and histamine (Patscheke et al, 1987;Battistini et al, 1990). Cumulative concentrations of ET-1 (1-100 nM) were added to intact and rubbed tracheal strips, the next concentration being added when the preceding one had reached a steady-state effect.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…In conclusion, our findings reveal a new aspect of PLA2-I action in lung as a possible mediator causing broncho-constriction in pulmonary diseases such as asthma [15]. We are now conducting further studies into its pathophysiological functions, as well as its target cells in lung tissue.…”
Section: Discussionmentioning
confidence: 99%